Experimental and theoretical study of the oblique impact of a tennis ball with a racket - Ghaednia, H.; Cermik, O.; Marghitu, D. B. (Proceedings of the Institution of Mechanical Engineers, Part P: Journal of Sports Engineering and Technology, 2015)
The normal and the oblique impact of a tennis ball with a racket has been studied. An accurate setup has been built in order to provide consistent initial conditions for the impacts. Experiments have been done for a wide range of impact angles and initial velocities. The motion of the ball before, during and after the impact has been recorded using a high-speed camera with 10,000?frames per second. The impact has been divided into two phases, compression and restitution. An expression for the contact force has been provided. The coefficient of restitution and effective coefficient of friction have been analyzed experimentally. For low impact velocities, the coefficient of restitution is constant at different impact angles. The effective coefficient of friction changes as a function of the impact angle. The contact force expression has been determined for the compression and the restitution phases using the experimental data from normal impact experiments. The simulation and experimental results are compared and verified for the normal and the oblique impacts.